Parental Involvement in Enhancing Intrinsic Motivation in EFL Learning in Indonesia - Muetia Maulisa; Sukri Adani (STMIK Indonesia Banda Aceh, 2025)
Parental involvement is a critical driver of student motivation and achievement worldwide, yet its specific role in fostering intrinsic motivation among Indonesian learners of English as a Foreign Language (EFL) remains underexplored. This systematic review examines 13 empirical studies published between 2019 and 2024, identifying five principal themes of parental engagement: academic support and resource provision, emotional and motivational involvement, parental beliefs and expectations, home environment and external influences, and learner autonomy with motivational outcomes. The analysis shows that parents who actively participate, providing resources, encouragement, and positive beliefs, significantly strengthen their children’s self-driven interest and persistence in English learning. Moreover, a supportive and stimulating home environment, alongside opportunities for autonomy, are found to be decisive factors in sustaining intrinsic motivation. The findings highlight the multifaceted mechanisms through which parental behaviors enable Indonesian EFL learners to internalize the value of English proficiency, emphasizing the necessity for educational policies and parental engagement programs that strategically cultivate these motivational pathways. Ultimately, leveraging these insights can enhance both instructional practices and learners’ long-term language outcomes.